A prophet like Moses (Deut 18:15, 18): the origin, history, and influence of the Mosaic prophetic succession - DeJong, David N. (Journal for the study of Judaism, 2022)
This book provides a comprehensive study of the interpretation of Deuteronomy's concept of the prophet like Moses. It traces the origin, history, and influence of the Mosaic prophetic succession in the Hebrew Bible, Early Judaism, and the New Testament.